ABOUT THE PROBLEMS OF HIGHER EDUCATION MODERNIZATION IN THE RUSSIAN FEDERATION - Batechko, N (Continuing Professional Education: Theory and Practice, 2019)
The article describes the main tendencies of reforming and modernization of higher educational sphere in Russian Federation. It was described the dynamics of changes in the structure of higher education in Russia, connected with the implementation of demands of Bologna process. Attention was paid at the legislative process of higher education in Russian Federation, innovations, connected with structuration and optimization of higher educational establishments. Were given the examples of federal special programs, collaborated by the Russian Federation Government with the aim of effective reproduction of scientific and scientificpedagogical staff and staying the youth in the spheres of science, education and high technologies, saving and succession of generations in science and education. Were analyzed the contradictions which are specific for the Russian higher school in the context of globalization and eurointegration processes. It was proved that modernization of the higher education sphere is a national task, the aim of the whole country that can be achieved as a result of effective collaboration of the whole society and the state. Were indicated the analogues and peculiarities that distinguish processes of higher education modernization of Russia and Ukraine. It was noted that accumulated and systemized experience about modernization of higher education sphere of Russian Federation can be applied to the development of the main tendencies of reforming and modernization of higher education sphere in Ukraine.